Significant renoprotective effect of telbivudine during preemptive antiviral therapy in advanced liver cancer patients receiving cisplatin-based chemotherapy: a case–control study. (December 2014) - Lin, Chih-Lang; Chien, Rong-Nan; Yeh, Charisse; Hsu, Chao-Wei; Chang, Ming-Ling; Chen, Yi-Cheng; Yeh, Chau-Ting
Abstract Objective. Cisplatin is a known nephrotoxic agent requiring vigorous hydration before use. However, aggressive hydration could be life-threatening. Therefore, in cirrhotic patients with advanced hepatocellular carcinoma (HCC) under cisplatin-based chemotherapy, the risk of nephrotoxicity increased. Because previous studies showed that long-term telbivudine treatment improved renal function in chronic hepatitis B virus (HBV) infected patients, we conducted a case–control study to evaluate the clinical outcome of telbivudine preemptive therapy in HBV-related advanced HCC patients treated by combination chemotherapy comprising 5-fluorouracil, mitoxantrone and cisplatin (FMP). Material and methods. From June 2007 to March 2012, 60 patients with HBV-related advanced HCC, all receiving the same FMP chemotherapy protocol, were enrolled. Of them, 20 did not receive any antiviral therapy, whereas the remaining 40 patients (sex and age matched) received telbivudine preemptive therapy. Results. Progressive decrease of aminotransferase levels (p < 0.05) and progressive increase of viral clearance rates (p < 0.001) were found in telbivudine-treated group. No drug resistance developed during the course of treatment. When compared with non-antiviral-treated patients, a significantly higher post-therapeutic estimated glomerular filtration rate (eGFR) was found in the telbivudine-treated group (p < 0.001). In patients with initial eGFR >100 ml/min (n = 34), the median overall survival was significantly longer in the telbivudine-treated group (12.1 vs. 4.9 months; p = 0.042). Conclusion. Preemptive use of telbivudine significantly prevented eGFR deterioration caused by cisplatin-based chemotherapy in HBV-related advanced HCC. In patients with initially sufficient eGFR level, telbivudine treatment was associated with a longer overall survival.